Pregnancy, pregnancy loss and the risk of cardiovascular disease in Chinese women: findings from the China Kadoorie Biobank - Peters, S; Yang, L; Guo, Y; Chen, Y; Bian, Z; Tian, X; Chang, L; Zhang, S; Liu, J; Wang, T; Chen, J; Li, L; et al. (BioMed Central, 2017)
Background Pregnancy and pregnancy loss may be linked to cardiovascular disease (CVD). However, the evidence is still inconsistent, especially in East Asians where reproductive patterns differ importantly from those in the West. We examined the associations of pregnancy, miscarriage, induced abortion, and stillbirth with CVD incidence among Chinese women. Methods In 2004-08, the nationwide China Kadoorie Biobank recruited 302 669 women aged 30-79 years from 10 diverse localities. During 7 years of follow-up, 43 968 incident cases of circulatory disease, 14 440 of coronary heart disease (CHD), and 19 925 of stroke (including 11 430 ischemic and 2 170 haemorrhagic strokes), were recorded among 289,573 women without prior CVD at baseline. Cox regression yielded multiple-adjusted hazard ratios (HRs) for CVD risks associated with pregnancy outcomes. Results Overall, 99% of women had been pregnant and among them 10%, 53%, and 7% reported having a history of miscarriage, induced abortion, and stillbirth, respectively. Each additional pregnancy was associated with an adjusted HR of 1.03 (95% CI: 1.02; 1.04) for circulatory disease. A history of miscarriage, induced abortion, and stillbirth, respectively, were associated with adjusted HRs of 1.04 (1.01; 1.07), 1.04 (1.02; 1.07), and 1.07 (1.03; 1.11) for circulatory disease. The relationship was stronger with recurrent pregnancy loss; adjusted HRs for each additional loss being 1.04 (1.00; 1.09) for miscarriage, 1.02 (1.01; 1.04) for induced abortion, and 1.04 (1.00; 1.08) for stillbirth. Conclusion Among Chinese women, increases in pregnancy, and a history and recurrence of miscarriage, induced abortion, and stillbirth are each associated with a higher risk of CVD.